Tibolone in hormone replacement therapy (part 1) - J. Jakimiuk, Artur; Tomaszewski, Jacek; Bogusiewicz, Michał (Menopause Review/Przegląd Menopauzalny, 2003)
Since over 40 years hormone replacement therapy (HRT) is a standard treatment for menopausal symptoms. Quality of life improvement caused by the use of HRT was regarded to be beneficial for bone and cardiovascular system. However, recent studies showed that the prolonged use of HRT may be associated with increased risk of breast cancer. Moreover, HERS and WHI trials changed accepted opinion on use of hormone therapy in the primary and secondary prevention of cardiovascular diseases. Tibolone, a drug acting by a unique mechanism, since 1988 has been widely used in over 70 countries. This review presents contemporary data on the effect of tibolone on the breast, bone, lipids and cardiovascular system.